2021
DOI: 10.1080/19490976.2021.1927633
|View full text |Cite
|
Sign up to set email alerts
|

Gut Akkermansia muciniphila ameliorates metabolic dysfunction-associated fatty liver disease by regulating the metabolism of L-aspartate via gut-liver axis

Abstract: The gut bacterium Akkermansia muciniphila has been increasingly recognized for its therapeutic potential in treating metabolic disorders, including obesity, diabetes, and metabolicdysfunctionassociated fatty liver disease (MAFLD). However, its underlying mechanism involved in its wellknown metabolic actions needs further evaluation. The present study explored the therapeutic effect and mechanism of A. muciniphila in intervening MAFLD by using a high-fat and highcholesterol (HFC) diet induced obese mice model. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
103
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 145 publications
(121 citation statements)
references
References 68 publications
(85 reference statements)
5
103
1
Order By: Relevance
“…In line with this, a recent in vivo study in mice confirmed that A. muciniphila inoculation not only promoted efflux of fatty acids through positive modulation of genes involved in hepatic lipid transport, but also resulted in a higher number of mitochondria. 60 Our hypothesis is further substantiated by recent research, including studies performed in our lab, showing that direct inoculation or indirect diet-mediated A. muciniphila enrichment in rodents activates a network of genes involved in lipid oxidation in adipose and liver tissue. 3 , 60–67 These include gene encoding for PPARα, peroxisome proliferator-activated receptor-gamma coactivator-1 alpha (PGC1α), and carnitine palmitoyl‐transferase I (CPT‐I).…”
Section: Discussionsupporting
confidence: 64%
See 2 more Smart Citations
“…In line with this, a recent in vivo study in mice confirmed that A. muciniphila inoculation not only promoted efflux of fatty acids through positive modulation of genes involved in hepatic lipid transport, but also resulted in a higher number of mitochondria. 60 Our hypothesis is further substantiated by recent research, including studies performed in our lab, showing that direct inoculation or indirect diet-mediated A. muciniphila enrichment in rodents activates a network of genes involved in lipid oxidation in adipose and liver tissue. 3 , 60–67 These include gene encoding for PPARα, peroxisome proliferator-activated receptor-gamma coactivator-1 alpha (PGC1α), and carnitine palmitoyl‐transferase I (CPT‐I).…”
Section: Discussionsupporting
confidence: 64%
“… 60 Our hypothesis is further substantiated by recent research, including studies performed in our lab, showing that direct inoculation or indirect diet-mediated A. muciniphila enrichment in rodents activates a network of genes involved in lipid oxidation in adipose and liver tissue. 3 , 60–67 These include gene encoding for PPARα, peroxisome proliferator-activated receptor-gamma coactivator-1 alpha (PGC1α), and carnitine palmitoyl‐transferase I (CPT‐I). PPARα is a key sensor of fatty acid flux whose activation, together with PGC1α, stimulated the expression of CPT-I isoform α.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…The bacterial DNA was extracted from the fecal pellets with a Guide S96 DNA kit (Tiangen, Beijing, China), according to the instructions of the manufacturer. PCR amplification was carried out using 16S rRNA primers targeting the variable region V3-V4: 5′-ACTCCTACGGGAGGCAGCA-3′ and 5′-GGACTACHVGGGTWTCTAAT-3′ ( 25 ). Sequencing libraries were constructed and paired-ended sequencing was conducted on an Illumina NovaSeq 6000 platform (Illumina, San Diego, CA, USA) at Biomarker Technologies Company (Beijing, China).…”
Section: Methodsmentioning
confidence: 99%
“…Akkermansia muciniphila is a human intestinal gram-negative anaerobic bacteria, with promising probiotic activities against many metabolic-related diseases such as obesity, diabetes, inflammatory bowel disease, etc. (3)(4)(5)(6)(7). Amuc_1100 (AM protein), a highly abundant pili-like membrane protein of A. muciniphila, partly recapitulates the beneficial effects of A. muciniphila (8,9).…”
Section: Introductionmentioning
confidence: 99%